Just me and my puppy - Mayer, Mercer 1943- (New York Golden Books, 1999)
Even though Puppy misbehaves, he makes a wonderful pet.
"Mercer Mayer's Little Critter"--P. [4] of cover.
Keywords: Dogs -- Juvenile fiction; Pets -- Juvenile fiction; Dogs -- Fiction; Pets -- Fiction